Regionality, Grotesque Realism and Nostalgia in Dennis Potter’s Blue Remembered Hills - James Dalrymple (Études Britanniques Contemporaines, 2025)
This article considers Dennis Potter’s Blue Remembered Hills (BBC, 1979) in relation to questions of representations of regional identity in British television drama. Part of a generation of working-class writers who would enjoy the fruits of social mobility and work in broadcasting, Potter would nonetheless return to his roots in The Forest of Dean, Gloucestershire, throughout his career. Much of his work for television features scenes that take place in the region, some of which makes extensive use of local dialect. This can be seen as part of a broader trend in theatre, film and television, dating back to the mid-to-late 1950s, that promoted writers from the provinces. Yet Potter was one of the few to do so for the West Country, correcting in the process popular misconceptions about the region. Blue Remembered Hills, despite the use of adults to play children, is considered one of his less experimental plays, drawing on his background in order to portray regional identity and vernacular with the kind of authenticity with which kitchen sink drama is often associated. Yet there are nevertheless hints of the kind of illusion-breaking self-reflexivity for which he is best known, and which suggest an engagement with nostalgia and the problematic process of remembering.